Reproductive Performance and Population Structure of Beef Cattle Under Smallholder Farming Systems in A Tropical Region - Yendraliza Yendraliza (Journal of Tropical Animal Science and Technology, 2026)
The increasing demand for beef demands sustainable growth in the beef cattle population, particularly in smallholder farming systems. Artificial insemination (AI) is a widely used reproductive technology to support population growth, but its success is strongly influenced by the reproductive performance of females and the structure of the livestock population. This study aimed to evaluate the reproductive performance of female cattle and analyze the structure of the beef cattle population in the Pangean District, Kuantan Singingi Regency. The study was conducted in January–February 2023 using a survey method through structured interviews with 120 cattle farmers and direct observation of 605 cattle. Reproductive performance data were obtained from AI records of 93 cattle in 2019 and 69 cattle in 2020. Parameters observed included service per conception (S/C), conception rate (CR), non-return rate (NRR), population structure by age and sex, and farmer characteristics. The results showed that the reproductive performance of female cattle in 2019 and 2020 was statistically significantly different (p<0.05). The S/C value increased from 1.80 in 2019 to 2.11 in 2020, while the CR and NRR values increased from 79% to 85%. The sex ratio of adult cattle of 1:2 (male:female) indicates a population structure that supports reproductive success. The majority of breeders are women (66.67%), are of productive age, have basic education, and have 5–10 years of livestock farming experience. It was concluded that the reproductive performance of beef cattle in Pangean District is quite good and supported by a relatively ideal population structure. However, strengthening reproductive management is still needed to increase the efficiency of the AI program.